Longitudinal Multiparametric Quantitative MRI Evaluation of Acute and Chronic Multiple Sclerosis Paramagnetic Rim Lesions - Elkady, Ahmed M.; Elliott, Colm; Fetco, Dumitru; Araujo, David; Karimaghaloo, Zahra; Ganzetti, Marco; Clayton, David; Craveiro, Licinio; Kazlauskaite, Agne; Narayanan, Sridar; Arnold, Douglas L.; Rudko, David A. (Journal of magnetic resonance imaging, 2025)
Background Multiple sclerosis (MS) paramagnetic rim lesions (PRLs) are markers of chronic active biology and exhibit complex iron and myelin changes that may complicate quantification when using conventional MRI approaches. Purpose To conduct a multiparametric MRI analysis of PRLs. Study Type Retrospective/longitudinal. Subjects Ninety‐five progressive MS subjects with at least one persistent PRL who were enrolled in the CONSONANCE trial. Field Strength/Sequence 3‐T/Susceptibility‐weighted, T1‐weighted, T2‐weighted, and fluid‐attenuated inversion recovery. Assessment Acute/chronic PRLs and non‐PRLs were measured at screening, 24, 48, and 96 weeks using quantitative magnetic susceptibility (QS), R2*, and standardized T1w/T2w ratio (sT1w/T2w). PRL analyses were performed for whole lesion, core, and rim. The correlations between PRL core and rim sT1w/T2w, QS, and R2* were assessed. Statistical Tests Linear mixed models. A P‐value <0.05 was considered significant. Results There was a significant decrease in sT1w/T2w (−0.24 ± −5.3 × 10−3) and R2* (−3.6 ± 2.2 Hz) but a significant increase in QS (+21 ± 1.3 ppb) using whole‐lesion analysis of chronic PRLs compared to non‐PRLs at screening. Tissue damage accumulated at the 96‐week time point was more evident in acute/chronic PRLs compared to acute/chronic non‐PRLs (ΔsT1w/T2w = −0.21/−0.24 ± 0.033/0.0053; ΔR2* = −4.4/−3.6 ± 1.4/2.2 Hz). New, acute PRL sT1w/T2w significantly increased in lesion core (+4.3 × 10−3 ± 1.2 × 10−4) and rim (+5.6 × 10−3 ± 1.2 × 10−4) 24 weeks post lesion inception, suggestive of partial recovery. Chronic PRLs, contrastingly, showed significant decreases in sT1w/T2w over the initial 24 weeks for both core (−2.1 × 10−4 ± 2.0 × 10−5) and rim (−2.4 × 10−4 ± 2.0 × 10−5), indicative of irreversible tissue damage. Significant positive correlations between PRL core and rim sT1w/T2w (R2 = 0.53), R2* (R2 = 0.69) and QS (R2 = 0.52) were observed. Data Conclusion Multiparametric assessment of PRLs has the potential to be a valuable tool for assessing complex iron and myelin changes in chronic active PRLs of progressive MS patients. Level of Evidence 2 Technical Efficacy Stage 3